Aerodynamic investigation of the start-up process of H-type vertical axis wind turbines using CFD. Issue 204 (September 2020) - Celik, Yunus; Ma, Lin; Ingham, Derek; Pourkashanian, Mohamed
Abstract: In this study, a CFD start-up model has been built after conducting the sensitivity studies to evaluate the self-starting behaviour of the H-type vertical axis wind turbines (VAWTs). The self-starting behaviour of a well-investigated VAWT is used for the model validation, and then the details of aerodynamics of the start-up process have been examined. Finally, the effect of the moment of inertia and the blade number on the aerodynamic behaviour of the self-starting and power performance of the H-type VAWT are analysed. It has been found that in the critical region, where TSR<1, the contribution of the drag to the torque generation plays a significant role in the second and third quarters of the rotor revolution, where the azimuthal position varies between 100° and 253°. The results also show that increasing the turbine inertia did not show a noticeable effect on the start-up behaviour of the turbine and final rotational speed. However, an increase in the instantaneous turbine power during the start-up process after the optimum TSR is observed with decreasing the turbine inertia. The current findings also show that an increase in the blade number makes the turbine easier to start-up; however, this may reduce the turbine power coefficient. Highlights: Aerodynamics of the start-up process of the H-type VAWT are investigated using the dynamic start-up model. In the critical region (TSR<1), the contribution of lift and drag to the turbine torque generations is investigated. The positive drag contributes to the torque generation in the second and third quarters of the rotor revolution when TSR<1. Increasing the moment of inertia does not show a noticeable effect on the starting of the turbine and the final speed. The larger number of blades allows the reaching of a slightly higher power coefficient at low tip speed ratios (TSR<1).